2019
DOI: 10.18806/tesl.v36i1.1305
|View full text |Cite
|
Sign up to set email alerts
|

Plurilingualism in Higher Education: A Collaborative Initiative for the Implementation of Plurilingual Pedagogy in an English for Academic Purposes Program at a Canadian University

Abstract: Previous literature on higher education suggests the inclusion of pedagogy that is linguistically and culturally inclusive in settings with increasing multilingualism, which is the case in Canada. Yet, little is known as to how the implementation of such pedagogy can take place, particularly in language programs. This article reports a researcher-instructor collaboration that aimed at implementing plurilingual practices, such as translanguaging, plurilingual identity, comparons nos langues, and intercomprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…A practical achievement of our study is the potential of moving instruction away from a monolingual tradition, addressing repeated calls made in TESOL (Kubota, 2016; May, 2014; Piccardo, 2013). However, it is important to note that teachers need to be supported by pedagogical materials and policies (Abiria et al, 2013; Galante et al, 2019; Piccardo & Galante, 2018)—even if these are internal school decisions—so that they can be open to plurilingual instruction and ensure that languages other than English are used in the classroom for pedagogical purposes. Another important achievement of this study is that it provides one manner of implementation in an English program, which may be replicated provided that necessary changes are made to suit the context and student population.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A practical achievement of our study is the potential of moving instruction away from a monolingual tradition, addressing repeated calls made in TESOL (Kubota, 2016; May, 2014; Piccardo, 2013). However, it is important to note that teachers need to be supported by pedagogical materials and policies (Abiria et al, 2013; Galante et al, 2019; Piccardo & Galante, 2018)—even if these are internal school decisions—so that they can be open to plurilingual instruction and ensure that languages other than English are used in the classroom for pedagogical purposes. Another important achievement of this study is that it provides one manner of implementation in an English program, which may be replicated provided that necessary changes are made to suit the context and student population.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Taken together, the plurilingual tasks challenged students to go beyond using the L1 only, which reflected the participant demographic; some students spoke Chinese as an L1 and had learned some Korean, Japanese, and French (the latter mainly due to exposure in Canada), whereas other students from Latin America spoke Spanish as an L1 and had some knowledge of Brazilian Portuguese and Indigenous languages from their own country. Their entire repertoire was activated to make meaning and develop awareness of communicative resources other than linguistic, such as gesture, drawings, volume, intention of the voice, and facial expressions, among others (for more information about the implementation of the plurilingual tasks, see Galante et al, 2019). The tasks are available on the website http://www.breakingtheinvisiblewall.com.…”
Section: Methodsmentioning
confidence: 99%
“…The study This was a mixed-methods study that included a quasi-experimental component with treatment and comparison groups in intact Academic Listening and Speaking (ALS) classrooms of an EAP program in Toronto, Canada. As part of a larger investigation of the implementation of plurilingual instruction (Galante et al 2019) and teachers' perceptions (Galante et al 2020), the study reported in this article focuses on data gathered from students only.…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of studies (e.g., Galante et al, 2019; Liu, Lo, & Lin, 2020; Ollerhead, 2019; Ollerhead, Crealy, & Kirk, 2020) have specifically probed into the impact of collaborative research approaches on translanguaging pedagogies in TESOL contexts. For instance, Liu et al (2020) found that teacher–researcher collaboration could be an effective professional development strategy for in‐service English teachers to problematize monolingual language ideologies and foster deeper understanding of translanguaging.…”
Section: Teacher–researcher Collaborationmentioning
confidence: 99%